Strategic Management of Tourist Services: Implications for Business Performance and Customer Satisfaction in Komodo National Park - Mahmudin, Tono (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the impact of tourist services and destination management on tourist satisfaction levels at Komodo National Park, Indonesia. The study employs a quantitative research design, collecting data through surveys from 320 tourists representing diverse demographics. Results reveal high levels of overall satisfaction, with service quality and destination management significantly influencing visitor perceptions. Accommodation facilities and conservation efforts receive positive ratings, while areas for improvement include information dissemination and visitor education. Regression analysis identifies service quality and destination management as key predictors of satisfaction. Qualitative insights highlight the park's unique appeal and opportunities for refinement. The study underscores the importance of integrated approaches to enhance visitor experiences and promote sustainability in ecotourism destinations like Komodo National Park.